2014
DOI: 10.1016/j.drugalcdep.2013.10.014
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure to the Lebanon War of 2006 and effects on alcohol use disorders: The moderating role of childhood maltreatment

Abstract: Background Civilian populations now comprise the majority of casualties in modern warfare, but effects of war exposure on alcohol disorders in the general population are largely unexplored. Accumulating literature indicates that adverse experiences early in life sensitize individuals to increased alcohol problems after adult stressful experiences. However, child and adult stressful experiences can be correlated, limiting interpretation. We examine risk for alcohol disorders among Israelis after the 2006 Lebano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
1
13
0
1
Order By: Relevance
“…This finding suggests that the experience of childhood maltreatment may confer a lasting sensitivity to later stressful life events, and is consistent with prior studies that have found a similar interactive effect on alcohol outcomes including heavy alcohol consumption (Young-Wolff et al, 2012, Keyes et al, 2012) and alcohol use disorders (Keyes et al, 2014). The growing number of adverse outcomes associated with stress sensitivity due to childhood maltreatment identified in the literature highlights a vulnerable population that warrants special attention for prevention and treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding suggests that the experience of childhood maltreatment may confer a lasting sensitivity to later stressful life events, and is consistent with prior studies that have found a similar interactive effect on alcohol outcomes including heavy alcohol consumption (Young-Wolff et al, 2012, Keyes et al, 2012) and alcohol use disorders (Keyes et al, 2014). The growing number of adverse outcomes associated with stress sensitivity due to childhood maltreatment identified in the literature highlights a vulnerable population that warrants special attention for prevention and treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In a U.S. twin sample (Young-Wolff et al, 2012), stressful life events were associated with heavier drinking among women exposed to childhood maltreatment than among those without such exposure. In a sample of Israeli adults, the risk for current alcohol use disorders was increased among those exposed to wartime stressors, but only among those with a history of childhood maltreatment (Keyes et al, 2014). In a predominantly African American community sample in Detroit, childhood maltreatment and neighborhood physical disorder were found to interact in predicting incident binge drinking (Keyes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural factors often influence beliefs about the cause and treatment of mental illness and shape the public attitudes toward people diagnosed with mental illness . Addressing the cultural beliefs associated with stigma against mental illness is of special importance in the Arab world, where most of the people diagnosed with mental illness suffer from war‐related mental health consequences and living in poverty . In addition, people diagnosed with mental illness living in the Arab word might refuse seeking formal psychological help due to cultural stigma .…”
Section: Introductionmentioning
confidence: 99%
“…6 Addressing the cultural beliefs associated with stigma against mental illness is of special importance in the Arab world, where most of the people diagnosed with mental illness suffer from war-related mental health consequences and living in poverty. 7 In addition, people diagnosed with mental illness living in the Arab word might refuse seeking formal psychological help due to cultural stigma. 2,8 Identification of the cultural attitudes and beliefs associated with stigma against mental illness has direct implications for culturally tailored interventions for reducing public stigma against mental ill-ness.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we conducted all analyses including salivary cortisol measures both with the full TSST sample as well as a subsample excluding non‐responders ( n = 10). Because childhood adversities have been shown to be related to both biological processes and alcohol use (Keyes et al ; Teicher & Samson ), we additionally analyzed respective associations with CTQ scores. Statistical inference was based on the robust Huber–White sandwich estimator of standard errors (Royall ) because this revealed considerably different results compared with conventional model‐based estimation of standard errors indicating that the robust method should be preferred.…”
Section: Methodsmentioning
confidence: 99%